2019
DOI: 10.1177/1527154419872834
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Blood Glucose Monitoring YouTube Video for Marshallese Patients Using a Community-Based Participatory Research Approach

Abstract: The purpose of this study was to (a) describe the development of a culturally appropriate glucose monitoring video using a community-based participatory research approach and (b) assess the cultural appropriateness and effectiveness of the video. The topic of the video—using a glucometer and the importance of performing blood glucose checks—was chosen by Marshallese community stakeholders. The video was produced in Marshallese with English subtitles and disseminated through YouTube. Participants were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…Our study endorses the notion that information sharing partnered with empowering people to generate their own solutions to the health issues have better outcomes in producing sustained behaviour changes, as well as, having an impact on peoples' lifestyles, particularly when they are supported by the community provider. Previous Pasifika studies (Powers et al 2015;McElfish et al 2019) have included other behavioural self-management approaches, such as videos and other aids have been effective and culturally appropriate to delay the development of, and manage conditions like T2DM. Nonetheless, our approach has been well supported by other studies (Baird et al 2014;Lawrence et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study endorses the notion that information sharing partnered with empowering people to generate their own solutions to the health issues have better outcomes in producing sustained behaviour changes, as well as, having an impact on peoples' lifestyles, particularly when they are supported by the community provider. Previous Pasifika studies (Powers et al 2015;McElfish et al 2019) have included other behavioural self-management approaches, such as videos and other aids have been effective and culturally appropriate to delay the development of, and manage conditions like T2DM. Nonetheless, our approach has been well supported by other studies (Baird et al 2014;Lawrence et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Social support and cultural factors can fortify social support networks, reinforce cultural identity, and enhance diabetes self-management [ 31 ]. One study that created and disseminated a glucose monitoring video in Marshallese with English subtitles achieved a 1.45% reduction in hemoglobin A1c ( p = 0.006) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wittenberg-Lyles et al (2015) reported that people who are experiencing the same difficult situation simultaneously and who are members of the same community of interaction end up helping one another by exhibiting greater tolerance levels than would be exhibited by a third party not experiencing the same situation. McElfish et al (2019) reported that developing education based on preventative actions requires the community to be included from the time at which the message is designed. Specifically, based on their study of Marshallese Americans, they report that creating a video featuring a participatory approach that is also recorded in the participants' native language can enable the dissemination of content adapted to this population, which can have a positive impact on patients in terms of their levels of knowledge, everyday practices, and health.…”
Section: Adapting the Message Conveyed To The Communitymentioning
confidence: 99%